2011
DOI: 10.1508/cytologia.76.137
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Studies of 4 Species of the Genus Kobresia (Cyperaceae) Collected from Nepal Himalaya

Abstract: Summary Chromosome numbers of 4 species of the genus Kobresia (Cyperaceae) collected from the Nepal Himalaya are reported. Chromosome numbers of K. curvata Kük. (2nϭ50), K. esenbeckii (Kunth) Noltie (2nϭ66), and K. duthiei C. B. Clarke (2nϭca. 84) are reported for the first time. Kobresia nepalensis (Nees) Kük. showed an unusually high chromosome number, 2nϭca. 114. It is concluded that chromosomal evolution in the unispicate Kobresia species may have been caused by both polyploidy and aneuploidy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Multiple origins from the same diploid progenitor species have been reported for bryophytes (Wyatt et al ., ), ferns (Ranker et al ., ) and angiosperms (Brochmann, Soltis & Soltis, ; Parisod & Besnard, ; Wu et al ., ), which have continuously increased intra‐autopolyploid diversity by introducing new maternal lineages (Soltis & Soltis, ). Therefore, even if we rejected an allopolyploid origin for K. pygmaea following Heilborn (), multiple origins from the same diploid ancestor or introgression from other species potentially played a role in the diversification history of K. pygmaea , and possibly in the entire genus (Waterway, ; Zhang, ; Yano et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Multiple origins from the same diploid progenitor species have been reported for bryophytes (Wyatt et al ., ), ferns (Ranker et al ., ) and angiosperms (Brochmann, Soltis & Soltis, ; Parisod & Besnard, ; Wu et al ., ), which have continuously increased intra‐autopolyploid diversity by introducing new maternal lineages (Soltis & Soltis, ). Therefore, even if we rejected an allopolyploid origin for K. pygmaea following Heilborn (), multiple origins from the same diploid ancestor or introgression from other species potentially played a role in the diversification history of K. pygmaea , and possibly in the entire genus (Waterway, ; Zhang, ; Yano et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The resulting diploid chromosome number 2 n = 52 is not a multiple of x = 16 or x = 18, and thus x = 26 may represent a third basic number. Chromosome numbers of K. curvata (2 n = 50, Yano et al ., ) and K. duthiei (2 n = c . 84, Yano et al ., ) could represent multiples (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combined application of chromosome counts, new microsatellite markers and flow cytometry confirmed tetraploidy in C. parvula (2n = 4x = 64) 5 . Chromosome numbers of Kobresia esenbeckii (2n = 66), Kobresia duthiei (2n = 84), Kobresia curvata (2n = 50), Kobresia schoenoides (2n = 32) were reported and it is concluded that chromosomal evolution in the unispicate Kobresia species may have been caused by both polyploidy and aneuploidy 6 .…”
Section: Introductionmentioning
confidence: 99%